Pengaruh, Arus Kas Bebas, Arus Kas Operasi dan Pajak terhadap Kebijakan Dividen pada Perusahaan yang Terdaftar di Jakarta Islamic Index - R. Suhaimi; Slamet Haryono (Jurnal Ilmiah Akuntansi dan Humanika, 2021)
This study will conduct research on the influence between the independent variables and the dependent variable. Where in this study will examine the effect of Free Cash Flow, Operating Cash Flow and Taxes as independent variables on dividends as dependend variable, which are the dependent variable using company data listed on the Jakarta Islamic Index for the priod 2017-2019. Research method by using multiple regression test data analysis model (multiple regression) to test the relationship or the effect of independent variable. The results showed that two of the three independent variables used, namely operating cash flow had a significant and significant effect on dividends and taxes also had a significant effect on dividends, while free cash flow had no effect on the dependent variable, namely dividends.